Multigene panel testing in Turkish hereditary cancer syndrome patients - ALAVANDA, CEREN; GÜNEY, AHMET İLTER (My University, 2022)
@ 2022 by the Istanbul Medeniyet University.Objective: Hereditary cancer syndromes (HCSs) are a heterogenous group of disorders caused by germline pathogenic variations in various genes that function in cell growth and proliferation. This study aimed to describe the germline variations in patients with hereditary cancer using multigene panels. Methods: The molecular and clinical findings of 218 patients with HCS were evaluated. In addition, 25 HCS-related genes were sequenced using a multigene panel, and variations were classified according to the American College of Medical Genetics and Genomics (ACMG) criteria. In total, 218 HCS patients predominantly with breast, colorectal, ovarian, gastric, and endometrium cancers were included. Results: Pathogenic variations in 12 distinct genes were detected in 36 of 218 (16.5%) cases. In this study, the most affected gene was the ATM gene, in which pathogenic variations were detected in 8 of 218 cases, followed by CHEK2 (3.2%), MUTYH (3.2%), BRIP1 (1.8%), BARD1 (0.9%), TP53 (0.9%), PALB2 (0.4%), MLH1 (0.4%), MSH2 (0.4%), PMS2 (0.4%), RAD50 (0.4%), and RAD51C (0.4%). Conclusions: This study contributes to genotype-phenotype correlation in HCSs and expands the variation spectrum by introducing three novel pathogenic variations. The wide spectrum of the gene pathogenic variations detected and the presence of multiple gene defects in the same patient make the multigene panel testing a valuable tool in detecting the hereditary forms of cancer and providing effective genetic counseling and family specific screening strategies.

Amaç: Herediter kanser sendromları (HCS) hücre büyümesi ve proliferasyonunda görevli genlerde saptanan germline mutasyonlardan kaynaklanan heterojen bir grup hastalıktır. Bu çalışmada kalıtımsal kanser sendrom ön tanısıyla değerlendirilen olgularda çoklu gen paneli ile germ hattı varyasyonlarının değerlendirilmesi planlanmıştır. Yöntemler: Kalıtımsal kanser sendromu düşünülen 218 olgudan periferik kandan DNA izolasyonu sonrası HCS ile ilişkili 25 gen multigen panel kullanılarak dizilendi ve varyasyonlar American College of Medical Genetics and Genomics (ACMG) kriterlerine göre değerlendirildi. Bulgular: Meme, kolorektal, over, gastrik ve endometriyum kanseri başta olmak üzere toplam 218 herediter kanser sendromlu olgu değerlendirildi. Tüm çalışma grubu incelendiğinde en sık ATM gen varyasyonları (8/218, %3,6) tespit edildi ve bunu sıklık sırasına göre CHEK2 (%3,2), MUTYH (%3,2), BRIP1 (%1,8), BARD1 (%0,9), TP53 (%0,9), PALB2 (%0,4), MLH1 (%0,4), MSH2 (%0,4), PMS2 (%0,4), RAD50 (%0,4), RAD51C (%0,4) varyasyonları takip etmekteydi. Sonuçlar: Bu çalışmada farklı kanser türlerinde kalıtımsal kansere yol açan genler analiz edilmiş ve fenotiple ilişkisi değerlendirilmiştir. Ayrıca bu çalışmada ilk kez saptanan üç yeni varyasyon ile literatüre katkı sağlanmaktadır. Patojenik varyasyon tespit edilen genlerin geniş dağılımı ve aynı hastada birden fazla genetik varyasyonun varlığı düşünüldüğünde, uygun genetik danışma ve aileye özgü tarama planlaması yapmak için çoklu gen taraması kalıtımsal kanser hastalarının değerlendirilmesinde hızlı ve etkin bir yöntem olarak görünmektedir.
Türk Toplumunda Kalıtsal Kanser Sendromu Hastalarında Çoklu Gen Panel Taraması
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Cancer predisposition; genetic counseling; hereditary cancer; next generation sequencing; Kanser yatkınlığı; genetik danışma; herediter kanser; yeni nesil dizileme